The Effect of Top and Bottom Start Sprint Training on the 50 Meters Freestyle Swimming Speed of Megalodon Swimming Athletes - Martinus Martinus; M. Wili Syahrendra; I Bagus Endrawan; Aprizal Fikri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The background of this research aims to analyze the effect of upper and lower start sprint training on 50 meters freestyle swimming speed in the megalodon swimming club. This type of research is a quasi-experiment. With a two groups pretest posttest research method. The subjects of this research were 14 male athletes from the KU-1 swimming club, divided into two groups, each group consisting of 7 people. The results of the study showed that the top and bottom sprint start training influenced the 50 meters freestyle swimming speed seen from the average and the paired t test hypothesis test on the pretest sprint start from the top getting an average value of 32.67 and the posttest sprint start from the top obtained a mean value of 30.29. The Paired Sample T-test on the sprint start from the bottom pretest obtained a mean value of 32.43 and the sprint start from the bottom posttest obtained a mean value of 31.86. The difference between the mean pretest and posttest sprint start from the bottom was 0.57, the independent sample t-test on the sprint start from the top group got a mean value of 30.29 and the sprint start from the bottom group got a mean value of 31.86. The average difference between sprint starts from the top and bottom is 1.57, which means there is a difference in swimming speed. An increase in the results of the 50 meters swimming speed occurred in the experimental group because the experimental group was given sprint start training from the top and bottom for 8 weeks repeatedly with training twice a week. Repeated 50 meters swimming training results in an increase in 50 meters freestyle swimming speed.